Sistem Informasi Manajemen Apotek Berbasis Web Menggunakan Metode Waterfall (Studi Kasus Apotek Mita Pharma Pematangsiantar) - Apriyani, Lia; Sirait, Hasanuddin; Situmorang, Idawati (Jurnal Bisantara Informatika, 2025)
Advances in information technology have had a significant impact in various sectors, including the health sector. Various health institutions such as hospitals, clinics, pharmacies, and health centers have utilized technology in improving the efficiency of accessibility services to health data. In improving service effectiveness, a pharmacy must have information technology to help manage existing drug data. Currently, the management information system at Mita Pharma Pharmacy is still carried out by manual recording into a book, resulting in inaccuracies in recording transactions and difficulties in monitoring drug stocks. Seeing these problems, a website-based pharmacy management information system is needed with the aim of simplifying the process of recording drug data, inputting drug sales, purchasing drugs and also making reports on pharmacies using the waterfall method. This system is designed using the PHP programming language. From the results of black box testing that has been carried out on the web-based pharmacy management information system, it is found that the system can overcome the problems faced as mentioned above, therefore it can be concluded that the designed system can provide convenience for the admin and pharmacy owner to manage all pharmacy operations as well as improving the accuracy of information regarding real time drug monitoring and assisting pharmacy management in making better decisions.